Qaddukal Al Mayyas: Unraveling Romance and Misintterpretstion Through Sternberg's Triangular Theory of Love - Antikha, Sindy; Hasyim , Muhammad (Dinasti Research, 2025)
This research aims to analyze the components of love in the song Qadduka Al Mayyas by Sabah Fakhri based on Robert J. Sternberg's love triangle theory. The love triangle theory explains the three feelings that produce love which include the elements of intimacy, passion and commitment. From these three combinations, what then results is love. This research also aims to identify the type of love depicted in the song's lyrics and clarify the misinterpretation that Qadduka Al Mayyas is a qashidah song. With a descriptive qualitative approach, this research uses text analysis to explore the meaning of lyrics as an expression of romantic love. The research results show that the element of intimacy is reflected through expressions of admiration and praise for charming physical beauty. Passion is seen from a deep emotional description of someone's attractiveness. The element of commitment is indicated through the intensity of deep respect and appreciation for the object of love. Based on these three components, the song Qadduka Al Mayyas is categorized as a form of romantic love aspect. This finding confirms that the song is not a prayer, but a work of art that reflects the culture of love in the Arab tradition.